Ultra-low-power wireless anchor load monitoring system based on internet of things technology. (October 2019) - Tong, J; Lee, T H; Lin, Y
Abstract: Ground anchoring is a popular method to stabilize the slope. It is essential for stability evaluation to measure the tension value of anchor from installed load cell. In this paper, a wireless anchor load measuring system is proposed for continuously on-site slope stability monitoring. Each anchor load cell is connected to a MCU-based acquisition unit and become a wireless IoT end-device. This system is scalable so the sensor deployment will be much more flexible than that in conventional data acquisition system. The excitation circuit, signal amplification and analog-to-digital conversion are completed by a small-size device next to the anchor so that very low-noise result can be obtained. Each measurement consumes less than 10mA·s so this device can be drive only by a 55mm*70mm*40mm solar power module. Verified by almost 3-year's on-site test, it is confirmed the proposed monitoring system can continuously capture and send one measurement per minute to the cloud server without any other electric power. The experimental and on-site test results show the practicability of proposed system and its reliability of long-term measurement. It has very high application potential on real-time slope stability monitoring by collecting and analyzing the load values of all installed anchors.